Oxidation of Crystalline Rubrene Films: Evidence of an Epitaxial Native Oxide Layer. Issue 23 (29th September 2017) - Raimondo, Luisa; Trabattoni, Silvia; Moret, Massimo; Masciocchi, Norberto; Masino, Matteo; Sassella, Adele
Abstract: Rubrene (RUB) is a benchmark organic semiconductor since the record exciton diffusion length and high charge carrier mobility are demonstrated in its orthorhombic single‐crystal phase. In this respect, great research efforts on the growth and study of crystalline RUB thin films, the most suitable choice for device applications, are made, even though its oxidation remains a still open problem. Here, the oxidation of crystalline RUB thin films is focused, by studying and modeling the so‐formed interface between RUB and its oxide. Optical spectroscopy carried out on freshly grown and aged crystalline RUB films gives evidence that oxidation occurs without altering the original crystal structure of the RUB films. To deeply analyze the process, a direct characterization of rubrene endoperoxide (RUBox) is proposed: after synthesizing a microcrystalline powder, its crystal structure and Raman response are determined. The joint results achieved on the RUBox powder and on aged RUB films demonstrate that RUBox forms as a crystalline native oxide layer with a well‐defined epitaxial interface with the underlying RUB. Finally, structural constraints at the RUBox/RUB interface are shown to limit surface oxidation, with the oxide acting as a passivation layer against further oxidation. Abstract : Rubrene (RUB), one of the most promising organic semiconductors, exhibits a high propensity to oxidation, affecting the material properties. Here, coupling the structural characterization of polycrystalline rubrene endoperoxide (RUBox) with the spectroscopic analysis of aged RUB crystalline thin films, the presence of RUBox is identified as an epitaxial native oxide layer forming at the RUB surface.